A diferença está na pele?: depoimentos de mulheres negras e brancas presas na Penitenciária Feminina de Sant ana - Biazeto, Ana Luiza de F. (2010)
This dissertation aims to analyze the life of incarcerated black women at the Sant ana s Women Penitentiary in São Paulo, Brazil. This research attempts to shed light on the reasons why black and white women are in this penitentiary examining the causes of their arrests and relating the results obtained in this study to propositional the starters to a policy geared to women prisoners and blacks. The high number of black women (black or mixed) in the Brazilian prison system and the case of a 15 years old from Pará who had over 20 men in her cell in Belém in November 2007, are matters that motivated this research . As a result of theoretical studies and interviews, it is noted that the presence of blacks in the prison system is a historical reality, despite changes in the governing laws over the years, continued racism has made it possible to analyze this historical process in the penal system. It is impossible to investigate the criminal matter without taking into account the variables of gender that accompany it. The circumstances in the penitentiary system of blacks and women are examples of social issues, which in order to be understood in Brazil and Latin America require critical studies of relevant fields and the historical and structural processes that established societies in the continent. The incarcerated black woman, therefore, is manifestation of a social issue. In this qualitative research, three black women and three white women were interviewed in order to find differences and similarities in their reports. The female inmates are housed in separate prisons according to their crimes with drug trafficking being the most common crime among the inmates. This study analyzed the meaning, interpretation and explanation of the content of the communication articulated during interviews, focusing on the following subjects: drug trafficking, social inequalities, skin color, and prejudice. This thesis has an enhanced purpose to shed light on key aspects that affect the incarcerated female population in Brazil and also helps to (re) construct female identities, even behind bars. Concerning black women, the act of (re) constructing their female and black identities is necessary for them to accept themselves. Consequently their acceptance of their own identities will allow for their individual progress and also the progress of their daughters. The (re) construction of female identities is an area which really needs to be strengthened and present within Brazilian history. In addition, another key emphasis of this study is the need for autonomy of the perception of the incarcerated female